Molecular Polyarsenides of the Rare‐Earth Elements. Issue 4 (16th December 2015) - Arleth, Nicholas; Gamer, Michael T.; Köppe, Ralf; Konchenko, Sergey N.; Fleischmann, Martin; Scheer, Manfred; Roesky, Peter W.
Abstract: Reduction of [Cp*Fe(η 5 ‐As5 )] with [Cp′′2 Sm(thf)] (Cp′′=η 5 ‐1, 3‐( t Bu)2 C5 H3 ) under various conditions led to [(Cp′′2 Sm)(μ, η 4 :η 4 ‐As4 )(Cp*Fe)] and [(Cp′′2 Sm)2 As7 (Cp*Fe)]. Both compounds are the first polyarsenides of the rare‐earth metals. [(Cp′′2 Sm)(μ, η 4 :η 4 ‐As4 )(Cp*Fe)] is also the first d/f‐triple decker sandwich complex with a purely inorganic planar middle deck. The central As4 2− unit is isolobal with the 6π‐aromatic cyclobutadiene dianion (CH)4 2− . [(Cp′′2 Sm)2 As7 (Cp*Fe)] contains an As7 3− cage, which has a norbornadiene‐like structure with two short As−As bonds in the scaffold. DFT calculations confirm all the structural observations. The As−As bond order inside the cyclo As4 ligand in [(Cp′′2 Sm)(μ, η 4 :η 4 ‐As4 )(Cp*Fe)] was estimated to be in between an As−As single bond and a formally aromatic As4 2− system. Abstract : Sandwich with arsenic filling : [(Cp′′2 Sm)(μ, η 4 :η 4 ‐As4 )(Cp*Fe)] and [(Cp′′2 Sm)2 As7 (Cp*Fe)], which are the first polyarsenides of the rare‐earth metals, are reported. [(Cp′′2 Sm)(μ, η 4 :η 4 ‐As4 )(Cp*Fe)] is also the first d/f‐triple decker sandwich complex with a purely inorganic aromatic middle deck.